HUBUNGAN PERSEPSI SISWA TENTANG GURU MATEMATIKA DENGAN HASIL BELAJAR MATEMATIKA SISWA - Najichun, Mohamad; Winarso, Widodo (Faculty of Psychology, Diponegoro University, 2016)
The purpose of this study was to know the relationship between student perception towards mathematics teacher with mathematics academic performace. The population of the study were all students of class VIII SMPN 8 Cirebon in the academic year 2014/2015, with the number of students 287 people. The sampling technique used proportional random sampling, and the sample size was 56 students. Data collection techniques used: 1) Questionnaire of Perceptions towards Mathematics teacher, and 2) The results of student mathematics learning test. The result of correlation analysis show no significant correlation between students perception towards teacher and academic performance (r= .155, p= .254).